Efektivitas Penerapan Transaksi QRIS Era Covid-19 di Pasar Tradisional Kota Batam Menurut Perspektif Hukum Progresif - Permatasari, Rika; Amboro, F. Yudhi Priyo; Nurlaily, Nurlaily (Fakultas Syariah INSURI Ponorogo, 2022)
In the Covid-19 era, the Minister of Public Health uses non-cash transactions, non-cash transactions that reduce direct interaction are the QRIS (Quick Response Code Indonesian Standard) payment system, with a QR Code Scan of successful payment transactions. So according to researchers, traditional markets in Batam city are places that often use cash transactions, so it is good if QRIS payments can be made in traditional markets. The research used by the researcher is empirical which goes directly to the field to see the market situation and how effective the implementation of QRIS is by conducting interviews with business actors in the traditional market. The researcher obtained data from DISPRINDAG, Bank Indonesia and Conventional Banks for effective implementation of QRIS in Traditional Markets because of the 51 Traditional Markets in Batam City only 3 traditional markets have implemented QRIS, so the solution is according to Government Progressive Law, Bank Indonesia and Conventional Banks that support QRIS must conduct socialization to traditional market businesses and the community to explain more clearly and help business actors who want to implement QRIS so that the implementation of QRIS can run effectively, and can suppress the transmission of Covid-19, at the Batam City Traditional Market by utilizing the non-cash payment method using QRIS